Contextual Expertise and the Development of Organization and Management Theory - Ali Aslan Gümüsay; John M. Amis (European Management Review, 2021)
Generating theory from research settings requires researchers to adeptly engage with the social intricacies of the field. They need to develop a contextual understanding by gaining in-depth insights into the setting, while retaining a critical distance from it. Researchers must practice this along the entire research journey, from site selection, through data collection and analyses, to theory development and explanation. However, contextual expertise has been assumed rather than actively considered as a critical component in organization and management studies. We lay out steps for understanding the nature of contextual expertise, offer systematic advice for research projects and outline methodological practices across the research process to choose, capture, comprehend, convey, and confirm contextual specificities. The growing social complexity of research settings renders the development of contextual expertise increasingly important for the generation of enriched and more diverse theory. It also has implications for organization and management studies as a scientific community.
Keywords: 650; contextual expertise; qualitative research; methodological rigor; research design; research context; research team